2010
DOI: 10.1017/s0007114510005039
|View full text |Cite
|
Sign up to set email alerts
|

Dietary oxidised frying oil causes oxidative damage of pancreatic islets and impairment of insulin secretion, effects associated with vitamin E deficiency

Abstract: We previously reported that, in rodents, a diet with a high oxidised frying oil (OFO) content leads to glucose intolerance associated with a reduction in insulin secretion. The present study aimed at investigating the impairment of pancreatic islets caused by dietary OFO. C57BL/6J mice were divided into three groups to receive a low-fat basal diet containing 5 g/100 g of fresh soyabean oil (LF group) or a high-fat diet containing 20 g/100 g of either fresh soyabean oil (HF group) or OFO (HO group). After 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
(84 reference statements)
1
19
0
Order By: Relevance
“…Similarly, in previous studies, heated oils by increasing production of reactive oxygen species caused glucose intolerance, pancreatic beta cell destruction, and reduced insulin secretion (11,22). In this study, no significant difference was found in HDL-C level between the groups yet TG and total cholesterol levels increased at the end of the study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, in previous studies, heated oils by increasing production of reactive oxygen species caused glucose intolerance, pancreatic beta cell destruction, and reduced insulin secretion (11,22). In this study, no significant difference was found in HDL-C level between the groups yet TG and total cholesterol levels increased at the end of the study.…”
Section: Discussionsupporting
confidence: 77%
“…Likewise, heating soybean oil for 3 hours increased fat mass while it reduced body weight of mice (7). Also, 8-week ingestion of high oxidized frying oil (205°C for four 6-hour periods) deteriorated insulin secretion from pancreatic islets (11).…”
mentioning
confidence: 98%
“… a Considering the difference observed in tocopherols in lipid mixtures, which can affect their metabolic impact [31], care was taken to supplement lipid mixtures with α-tocopherol during formulation to achieve iso-tocopherol diets.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular nature, toxicities and health hazards potentially presented by aldehydic LOP toxins have been previously explored in some detail, as have analytical strategies available for their determination and monitoring, e.g., in fried food sources, and human/animal biofluids and tissues, for probing their in vivo absorption, biodistribution, metabolism and urinary excretion (an example of the 1 H NMR analysis of aldehydes, specifically LOPs and vanillin, in a typical non-fried food product is shown in Figure 4). Indeed, the toxicological and pathogenic properties conceivably arising from the ingestion of aldehydic LOP-containing COs heated according to standard frying practices (in the form of CO-absorbing fried foods for humans), and also aldehyde model systems, include their potential roles in the development and perpetuation of cardiovascular diseases [54][55][56], their carcinogenic [57][58][59][60][61], gastropathic [62], pro-inflammatory [63], and teratogenic properties [64], contributions towards neurodegenerative disorders [65], their hypertensive effects [66]; the development and perpetuation of diabetes [67];and respiratory and pulmonary complications, the latter especially for acrolein [68]; this list is inexhaustive. The inhalation of volatile aldehydes and other carbonyl compounds by workers employed in poorly-ventilated fast-food/restaurant retail outlets is also considered to pose a major threat to human health [69], particularly with reference to established links between an increased incidence of lung cancer and cooking oil fume inhalation amongst such personnel [13,[70][71][72].…”
Section: Secondary Aldehydic Lops: Dietary Ingestion Gastrointestinamentioning
confidence: 99%